(untitled) - Vietnam; Socialist Republic (Hanoi, 1996)
The report provides a presentation of data collected, analyses performed, geographical, economic and social descriptions and findings as well as recommendations for consideration in further planning for development of the fiheries sector.
Keywords: Fish culture,Fish culture,Nuôi cá; Economic aspects,Social aspects,Khía cạnh kinh tế; Vietnam,Việt Nam